Selection and characterisation of an HD1‐like Bacillus thuringiensis isolate with a high insecticidal activity against Spodoptera littoralis (Lepidoptera: Noctuidae). Issue 8 (22nd October 2013) - Azzouz, Hichem; Kebaili‐Ghribi, Jihene; ben Farhat‐Touzri, Dalel; Daoud, Fatma; Fakhfakh, Ines; Tounsi, Slim; Jaoua, Samir
Abstract BACKGROUND Spodoptera littoralis (Boisduval) larvae are known by their susceptibility to Bacillus thuringiensis subsp. aizawai strains. In order to prevent the appearance of B. thuringiensis (Bt) resistance and to develop economical Bt‐based biopesticides, the selection and the characterisation of a B. thuringiensis isolate toxic against S. littoralis larvae and overproducing δ‐endotoxins were investigated. RESULTS Among 124 Tunisian B. thuringiensis isolates assessed against S. littoralis larvae, four isolates showed toxicity similar to and higher than the toxicity of the aizawai strain HD133 and the kurstaki strain HD1 respectively. The plasmid pattern of the selected isolates was similar to that of HD1. Polymerase chain reaction (PCR) analysis using specific primers revealed that these isolates present different gene contents. The only detected gene encoding Spodoptera‐specific toxin was cry9. The selected isolates were found to produce bipyramidal and cubic crystals. The assessment of δ‐endotoxin production by these isolates showed that BUPM28 produced 43.71 and 80.81% more δ‐endotoxin than HD1 and HD133 respectively. The application of osmotic or heat shock stress on the BUPM28 isolate made it possible to enhance δ‐endotoxin production by 22 and 23% respectively. CONCLUSION On the basis of its potent insecticidal activity and its high level of δ‐endotoxin production, the BUPM28 isolate can be considered to be an effective alternative for the control of S. littoralis. © 2013 Society of Chemical Industry